2005
DOI: 10.1521/scpq.2005.20.3.318
|View full text |Cite
|
Sign up to set email alerts
|

Academic crime and punishment: Faculty members' perceptions of and responses to plagiarism.

Abstract: Academic dishonesty and its consequences have become increasingly complex. Highly accessible electronic media, profound consequences for misconduct and reporting, and lack of standard practice intensify the issues. We surveyed 270 faculty members to determine whether they had been confronted with plagiarism and if they felt prepared to deal with it. Using case studies, we examined faculty characterizations of the severity of students' uncited use of another's work, and their suggested actions, reports, and san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 18 publications
1
26
0
1
Order By: Relevance
“…However, very few students are actually involved (0.1 % in 2004) in academic disciplinary cases (Colnerud & Rosander, 2009). It is important to note that although governance and reporting structures can track and report this behavior, disciplinary activities are subjective, contingent on the opinions and judgment of faculty or other members of the academic institution (Robinson-Zañartu et al 2005). …”
Section: Disciplinary Governance Structure and Academic Dishonesty Inmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very few students are actually involved (0.1 % in 2004) in academic disciplinary cases (Colnerud & Rosander, 2009). It is important to note that although governance and reporting structures can track and report this behavior, disciplinary activities are subjective, contingent on the opinions and judgment of faculty or other members of the academic institution (Robinson-Zañartu et al 2005). …”
Section: Disciplinary Governance Structure and Academic Dishonesty Inmentioning
confidence: 99%
“…McCabe (2005) assessment of almost 10,000 faculty members from 2002 to 2004 showed that 44 % of those who were aware that their students engaged in cheating over that time period had never reported a student for cheating to the appropriate campus authority. According to a study based on 842 faculty members' perceptions of responses to plagiarism, perceptions of severity of the offense strongly mediated the consequence that they recommend (Robinson-Zañartu et al 2005). …”
Section: Review Of Literaturementioning
confidence: 99%
“…According to the National Center for Education Statistics [17], almost 4.3 million undergraduate students are participating in online courses per year. There is a notion that it is easier to cheat when participating in distance learning classes [18], and both students and faculty are aware of the intensity of this phenomenon compared to traditional courses [11], particularly where there is little or no personal contact between students and faculty [19], [20]. Similarly, Kelley and Bonner [21] suggested that students who feel close to their professors tend to be more honest.…”
Section: Introductionmentioning
confidence: 99%
“…Esto sucede más a menudo cuando alumnos con un desempeño menos positivo perciben menos monitoreo/supervisión de los maestros, en clases más teóricas (Comas-Forgas, y Sureda-Negre, 2010), y cuando perciben penas inferiores (Teixeira y Rocha, 2010). Realmente, algunos estudios han demostrado que, con respecto a las sanciones previstas, aunque existen diferentes prácticas que van hasta la expulsión de la escuela (especialmente en la educación superior) (Robinson-Zañartu et al, 2005), la mayoría de los alumnos y los profesores tienden a percibir sanciones más frecuentes como un reproche o descuento en la En un intento de dar un paso más en el análi-sis, hemos tratado de explorar la relación entre estas conductas inadaptadas, los abordajes al aprendizaje y la creatividad. Es decir, tratamos de entender si los alumnos que hacen plagio tienen una conducta más superficial frente al estudio y son menos creativos sobre las situaciones de logro.…”
Section: Introductionunclassified